Information storage technologies in the digital environment - Vázquez-Moctezuma, Salvador E. (2015)
Libraries have long functioned as information repositories, providing access to it by collecting and preserving data. In the present, environment has changed, so libraries are challenged to contain an increasing volume of digital information, hence the massive information technologies are needed. The aim of this paper is revising methods of storage systems for massive data; therefore, four types of data storage technologies, which are DAS, NAS, SAN and cloud storage are described and analyzed using the documentary method. It was found scarce literature on digital storage systems viewed from the perspective of information science; for this reason, publications in the field of computer science and engineering systems were used in order to understand the topic. It is concluded that storing data in the digital age is carry out in concentrated and distributed form.